Developing Gamification Strategies to Boost English Speaking Skills: Manuscript Submission: Developing Gamification Strategies to Boost English Speaking Skills - Nur Shiyam Mendrofa; Malili Zebua; Lefis Niwati Gulo; Puspa Triyani Waruwu; Fitriyana Purnama S. Laowo; Siti Khafifah Shaleh N.Cui; Muharni Sartika Zebua; Yaredi Waruwu (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Speaking skill is a crucial component of English language learning; however, many EFL students experience anxiety, low confidence, and limited opportunities to practice oral communication. This study aims to develop gamification strategies to boost English speaking skills among third-semester students of the English Education Study Program at Universitas Nias. The study employed a Research and Development (R&D) design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were ten students selected from one class with a total population of thirty-eight students. Data were collected through speaking tests, observation checklists, questionnaires, and documentation. The findings indicate that the developed gamification strategies increased students’ motivation, participation, confidence, and speaking fluency. These results suggest that gamification, when systematically designed, can serve as an effective instructional strategy for improving English speaking skills in higher education EFL contexts.